Hubungan Integritas Auditor, Pengalaman dan Profesionalisme terhadap Kinerja Audit - Rizal Mawardi; Nilakandita Maryam (JABI (Jurnal Akuntansi Berkelanjutan Indonesia), 2023)
This study aims to analyze the influence of the variables Auditor Integrity, Experience and Professionalism on Audit Performance. The research method used is a quantitative approach. The data used in this study are primary data in the form of a survey method, namely by distributing questionnaires to auditors who work at the Public Accountant Firm in Jakarta. The results of this study show that professionalism has a significant positive effect on auditor performance first. These results have implications for and support agency theory, where substantively professionalism shows a high level of work behavior in accordance with the code of ethics of the auditor's profession can increase public trust in the services provided by the auditor so that the professionalism of the auditor can be seen from the ability of the auditor, auditor's honesty, and responsibility. Second, the Work Experience Indicator shows a significant positive effect on audit performance. This provides evidence that the more experience the auditor has, the more it will influence his audit performance and the more he can find misstatements or audit risks in the field of a client effectively when carrying out his duties. The limitation in this study is the duration of the distribution of the questionnaire which coincides with the high season of work at Public Accountant Firm so that the number of respondent data does not reach the target